What does it mean to have experienced the death of a relative in a context of social and funeral restrictions? Lessons from the pandemic for bereavement research and clinical practice - Camille Boever; Emmanuelle Zech; Laurence Arcand; Chantal Verdon (PLoS ONE, 2025)
The circumstances of the Covid-19 pandemic raised concerns about their impact on people who were bereaved in this period. Numerous studies have attempted to quantify this impact. However, they have often adopted a pathologizing perspective on grief, with little attention being paid to the mediating processes and to the diversity of experiences, and their results have appeared contradictory. This study takes a comprehensive approach to understand these experiences in their uniqueness, without pathologizing them. Interviews with 12 bereaved people were analyzed using an interpretative phenomenological analysis and drawing on the theoretical framework of meaning-making, to explore the meanings that they gave to their loss and grief in a context of social and funeral restrictions. In our findings, the context of the pandemic appeared to be completely incompatible with the field of dying and mourning, creating paradoxical injunctions for some participants. While this led to feelings of guilt, powerlessness and loss of meaning for some, others were able to experience meaningful moments and to find solace in the farewell. All experiences were far from what had been expected, for better or for worse, and participants had to find their own ways to make sense of these unexpected experiences. The meanings they gave were complex, combining different levels of meaning – personal, moral, societal, or existential – and evolved over time, as did their emotional experiences. The results highlight the notions of paradoxical injunctions and grieving for an ideal goodbye as relevant for understanding and supporting the bereaved, drawing avenues for therapeutic work (e.g., restoring agency by providing a secure space to create a meaningful rite). They also have implications for research, highlighting the need to broaden the understanding of “impact”, to include mediators assessing subjectivity, and to privilege person-centered qualitative and quantitative methods.